Hubungan antara Perencanaan Keuangan dan Literasi Keuangan terhadap Investasi pada Pelaku UMKM di Kabupaten Lombok Tengah - Muhtarom, Zamroni Alpian; Anwar, Adrianda; Abdurrahman, Abdurrahman; Roodhi, Mohammad Najib; Genadi, Yeldy Dwi (Lembaga Yasin AlSys, 2025)
Micro, Small, and Medium Enterprises (MSMEs) contribute significantly to economic growth in Indonesia, particularly in Central Lombok Regency. However, longstanding issues such as weak financial planning and low financial literacy pose major obstacles in business management and effective investment decision-making. This study aims to examine the relationship between financial planning and financial literacy on the investment decisions of MSME actors. A quantitative approach was employed through a survey of 100 MSME actors in Central Lombok. Data were analyzed using multiple linear regression. The results indicate a significant influence of financial literacy and financial planning on the investment decisions of MSME actors. These findings have important implications for local governments and financial institutions in designing more targeted financial education programs to support MSME development.